2007
DOI: 10.1007/s11239-007-0153-2
|View full text |Cite
|
Sign up to set email alerts
|

The recognition of acute coronary ischemia in the outpatient setting

Abstract: A majority of patients with subsequent AMI visit an outpatient provider in the month preceding AMI. However, few present with symptoms of coronary ischemia in the outpatient setting (10%) and these symptoms are not always identified as such.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The benefits of early recognition and treatment of the deteriorating patient are well recognised (NPSA 2007) and transgress many specialties including management of sepsis (Rivers et al 2001), myocardial infarction (Jaffrey et al 2009) and stroke thrombolysis (Calleja et al 2009). Mortality rates can be significantly reduced for patients if they are identified before they deteriorate to cardio-respiratory arrest (NICE 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of early recognition and treatment of the deteriorating patient are well recognised (NPSA 2007) and transgress many specialties including management of sepsis (Rivers et al 2001), myocardial infarction (Jaffrey et al 2009) and stroke thrombolysis (Calleja et al 2009). Mortality rates can be significantly reduced for patients if they are identified before they deteriorate to cardio-respiratory arrest (NICE 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the time span before the ACS to define preceding chest pain, on the setting (outpatient vs. inpatient), and on the methodology used in other studies, the prevalence of chest pain before ACS varied [4,5,19] and was higher for patients with non-ST elevation acute myocardial infarction, in accordance with our results [20]. A proportion of 61% for chest pain in the previous 6 months is similar to previous findings from the 1970s [2].…”
Section: Discussionmentioning
confidence: 99%
“…Referral to ECG was used as a surrogate for the intention of further investigation of possible cardiac chest pain, as this exam is the cornerstone of the initial evaluation of patients whatever the type of health institution sought and is easily identified by patients. The low rates of performance of an ECG or other testing modalities, including exercise stress test (which was also low for the subgroup of patients who reported that pain was cardiac in origin), and the absence of performance of myocardial perfusion scintigraphy and coronary angiography, favor that inaccurate noninvasive coronary ischemia testing may be one of the factors contributing to the misdiagnosis of symptoms of myocardial ischemia [4]. Furthermore, the type of noninvasive test performed for diagnosing CHD suggests that the choice of the exam largely depended on physician preference and/or local availability [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations